Fixed-ratio combination therapy for type 2 diabetes: the top ten things you should know about insulin and glucagon-like peptide-1 receptor agonist combinations. Issue 4 (19th May 2018) - Blumer, Ian; Pettus, Jeremy H.; Santos Cavaiola, Tricia
ABSTRACT: Many individuals with type 2 diabetes (T2D) will eventually require insulin therapy to help achieve and maintain adequate glycemic control. However, the use of insulin can be associated with adverse effects such as hypoglycemia and weight gain, and in some patients the addition of insulin to treatment regimens is often still insufficient to achieve target glycemic control. Combining basal insulin with a glucagon-like peptide-1 receptor agonist (GLP-1 RA) for the treatment of patients with T2D has been demonstrated to be effective and well tolerated, while mitigating many of the adverse events associated with giving either of these drug classes alone. Two titratable, fixed-ratio combination therapies, iGlarLixi and IDegLira, that combine basal insulin and a GLP-1 RA in a once-daily subcutaneous injection are currently approved by the US Food and Drug Administration (FDA) for the treatment of patients with T2D. The fixed-ratio combination iGlarLixi combines insulin glargine 100 Units/mL with lixisenatide, while IDegLira combines insulin degludec 100 Units/mL with liraglutide. While these new fixed-ratio combinations contain antihyperglycemic medications that are familiar to most health care providers, there are many questions relating to their use when formulated as a fixed-ratio combination therapy. This article discusses the 'top 10' considerations that health care providers should know about these novel combination therapies as these agents begin to gain an increasing presence in clinical practice.